AB0589 Steroid-sparing effect of tocilizumab in the treatment of rheumatoid arthritis. (23rd January 2014) - Maeda, Y.; Ohshima, S.; Yoshimura, M.; Watanabe, A.; Tanaka, E.; Tsuji, S.; Harada, Y.; Matsushita, M.; Katada, Y.; Hashimoto, J.; Saeki, Y.
Abstract : Background: Long-term use of corticosteroid is often required in rheumatoid arthritis(RA), but it is suggested that dose dependent relationship between prednisone treatment and the risk of pneumonia in RA patients 1 . Therefore, reducing corticosteroid use may improve the safety profile. Moreover, because long term use of corticosteroid increases adverse events such as osteoporosis, diabetes mellitus, hyperlipidemia, it is better to taper corticosteroid dose as rapidly as clinically feasible. Objectives: To evaluate the steroid-sparing efficacy of tocilizumab(TCZ) compared with infliximab(IFX) in RA. Methods: Ninety-five RA patients (TCZ n=55; IFX n=40) were enrolled this study from our medical center between 2005 and 2011.The disease activity assessed by DAS28ESR, and prednisolone(PSL) dose were monitored at baseline and after 26, 54weeks. In addition, we evaluated total cholesterol, several bone biochemical markers such as serum crosslinked N-telopeptide of type I collagen (NTx), urinary NTx, and serum osteocalcin(OC) at the same time. Results: Baseline characteristics were similar in the 2 groups. Mean age was 59.9±13.5, 58.2±12.5 y, and the mean duration of disease was 11.4±10.1, 9.8±10.0 y in the TCZ and IFX groups, respectively. Disease activity was significantly reduced at week26, week54 compared with baseline in both groups (P<0.001). The mean DAS28ESR at week26 in TCZ-group was significantly decreased compared with that in IFX-group(Fig. 1 ). Steroid utilization in TCZ-group could be significantly more reduced compared with that in IFX-group (Fig. 2). Moreover, 24 patients (43.6%) in TCZ-group and 10 patients (25.0%) in IFX-group could discontinued PSL at week54. On the other hand, TCZ treatment significantly decreased the level of urinary Ntx than IFX at week26 and week54 (Fig. 3). There were no statistically differences in the levels of T-cho, and serum Ntx, serum OC at 26, 54weeks between 2 groups. Conclusions: Both TCZ and IFX were effective steroid-sparing agent for patients with RA. In addition, TCZ might have superior steroid-sparing efficacy compared to IFX. Furthermore, the mean level of urinary Ntx significantly decreased by TCZ treatment at week26 and week54. Taken together, this steroid-sparing efficacy might improve systemic bone metabolism. References: Frederick Wolfe, et al. Treatment for Rheumatoid Arthritis and the Risk of Hospitalization for Pneumonia. Arthritis and Rhumatism 2006;54:628-634. Disclosure of Interest: None Declared